Glass strengthening method and strengthened glass
By first performing alkali treatment of the alkali etching liquid in the glass strengthening method, and then using organic acid treatment liquid for acid treatment, the problem of low impact resistance improvement of traditional methods is solved, efficient glass strengthening is achieved, and impact resistance and yield rate are improved.
Patent Information
- Application Number
- CN202411960413.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-01
AI Technical Summary
Traditional glass strengthening methods have lower impact performance improvements, and as the processing time increases, the yield of the product will be adversely affected.
The base glass is treated with alkaline etching liquid, and then the pretreated glass is treated with acid. The organic acid treatment solution includes water and organic acids, which reconnect the broken silicon oxygen bonds through dehydration and condensation reaction, improving the integrity and rigidity of the microstructure of the glass surface.
It effectively improves the impact resistance of glass, while maintaining a high yield rate, significantly improving the strength and impact resistance of glass.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass processing, and in particular to a glass strengthening method and strengthened glass. Background Art
[0002] After the glass is cut, CNC processed and polished, a large number of micro cracks will appear on its surface. The presence of these micro cracks will greatly reduce the strength of the glass.
[0003] At present, traditional technology often uses strong alkali or acidic solution containing fluoride ions to remove micro cracks on the glass surface through etching to improve the strength of the glass. However, if a product with higher impact resistance is required, the alkali or acid treatment time needs to be extended. As the treatment time increases, it will have an adverse effect on the product yield, and the glass strengthening effect obtained by the above method is limited. Summary of the invention
[0004] Based on this, it is necessary to provide a glass strengthening method and strengthened glass to overcome the disadvantage that the traditional treatment method has a low improvement in the impact resistance of the glass.
[0005] In a first aspect of the present application, a glass strengthening method is provided.
[0006] A glass strengthening method comprises the following steps:
[0007] Using an alkaline etching solution to perform an alkali treatment on the base glass to obtain a pre-treated glass;
[0008] Performing acid treatment on the pretreated glass using an organic acid treatment solution;
[0009] The organic acid treatment solution includes water and an organic acid.
[0010] In some embodiments, the content of the organic acid is 3% to 15% by mass of the organic acid treatment solution.
[0011] In some embodiments, the alkaline etching solution comprises the following components in mass percentage:
[0012] Alkali 5%~50%;
[0013] Chelating agent 1%~10%; and
[0014] Water 40%~94%.
[0015] In some embodiments, the base comprises one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and potassium ethoxide; and / or
[0016] The chelating agent includes one or more of sodium citrate, disodium edetate and sodium gluconate.
[0017] In some embodiments, the acid treatment time is 2 min to 180 min; and / or
[0018] The temperature of the acid treatment is 50°C to 90°C; and / or
[0019] The alkali treatment time is 30min to 120min; and / or
[0020] The temperature of the alkali treatment is 50°C to 90°C.
[0021] In some embodiments, the organic acid includes one or more of hydroxyethylidene diphosphonic acid, citric acid, itaconic acid, m-phenylenedisulfonic acid, aminotrimethylphosphonic acid, ethylenediaminetetramethylphosphonic acid, phosphonic acid butylamine-1,2,4-tricarboxylic acid, tartaric acid, maleic acid, oxalic acid, malonic acid, 1,4-butanedisulfonic acid and methyl disulfonic acid.
[0022] In some of the embodiments, the organic acid treatment solution further comprises 1% to 30% of an organic solvent, based on the mass percentage of the organic acid treatment solution.
[0023] In some of the embodiments, the organic acid treatment solution further comprises 0.3% to 5% of a fluorine-free inorganic strong acid, based on the mass percentage of the organic acid treatment solution.
[0024] In some embodiments, the organic acid includes one or more of aminotris(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), phosphonic acid butylamine-1,2,4-tricarboxylic acid, tartaric acid, maleic acid, oxalic acid, malonic acid, 1,4-butanedisulfonic acid and methyl disulfonic acid;
[0025] Calculated by mass percentage of the organic acid treatment liquid, the organic acid treatment liquid further includes 1% to 30% of an organic solvent and 0.3% to 5% of a fluorine-free inorganic strong acid.
[0026] In a second aspect of the present application, a tempered glass is provided.
[0027] A tempered glass is obtained by using the above-mentioned glass tempering method.
[0028] In the above-mentioned glass strengthening method, the base glass is first treated with an alkaline etching solution, which can initially improve the microcracks on the glass surface and make the surface of the pre-treated glass rich in silicon-oxygen bonds or silicon hydroxyl groups. After the alkaline treatment, the pre-treated glass is treated with an organic acid treatment solution. Under the action of the organic acid, the broken silicon-oxygen bonds on the surface of the pre-treated glass are reconnected through a dehydration condensation reaction, which can further improve the integrity and rigidity of the microstructure of the glass surface and effectively enhance the impact resistance of the strengthened glass. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0030] In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In this application, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc.
[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0032] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0033] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0034] In this application, "above" or "below" includes the number itself. For example, "1 below" includes 1.
[0035] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0036] After the glass is cut, CNC processed and polished, a large number of micro cracks will appear on its surface. The presence of these micro cracks will greatly reduce the strength of the glass.
[0037] Traditional technology often uses strong alkali or acidic solution containing fluoride ions to remove microcracks on the glass surface through etching to improve the strength of the glass. For example, when using hydrofluoric acid etching, the main reactions are as follows:
[0038] SiO2 + 6HF → SiF6 2− +2H + + 2H2O
[0039] However, this treatment method has limited effect on improving the strength of the glass, and as the treatment time increases, excessive etching will have an adverse effect on the yield of the product.
[0040] In view of the shortcomings of traditional strengthening methods, some embodiments of the present application relate to a glass strengthening method, which can be used to obtain strengthened glass with good impact resistance and high yield.
[0041] A glass strengthening method comprises the following steps:
[0042] Using an alkaline etching solution to perform an alkali treatment on the base glass to obtain a pre-treated glass;
[0043] The pretreated glass is subjected to an acid treatment using an organic acid treatment solution.
[0044] The organic acid treatment solution includes water and an organic acid.
[0045] The glass strengthening method of the present application first uses an alkaline etching solution to perform an alkali treatment on the base glass, and through the reaction of the alkaline reagent with silicon dioxide, the purpose of reducing microcracks on the glass surface is achieved, thereby improving the impact resistance of the glass.
[0046] In some of the embodiments, the alkaline etching solution includes, by mass percentage, 5% to 50% of alkali, 1% to 10% of chelating agent, and 40% to 94% of water.
[0047] Optionally, the alkali content of the alkaline etching solution can be, in mass percentage, but is not limited to, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or other values within the range of 5% to 50%.
[0048] Optionally, in terms of mass percentage, the content of the chelating agent in the alkaline etching solution may be, but is not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or other values within the range of 1% to 10%.
[0049] Optionally, the alkaline etching solution consists of 5% to 50% of alkali, 1% to 10% of chelating agent and 40% to 94% of water in mass percentage.
[0050] The alkaline etching solution of the present application belongs to an alkaline polishing system. Compared with the acidic polishing system using highly dangerous hydrofluoric acid or concentrated sulfuric acid as an etchant, the alkaline polishing system is less harmful to the health of operators and is also more environmentally friendly. The alkali content of the alkaline etching solution has a great influence on the effect of the alkali treatment. If the alkali content is low, the effect of the alkali treatment is not obvious, and the improvement of the glass strength is relatively small; if the alkali content is too high, the hydroxide ions will continue to erode the surface of the glass after removing the microcracks on the surface of the product, which will reduce the strength of the glass.
[0051] In some embodiments, the chelating agent of the alkaline etching solution includes one or more of sodium citrate, disodium ethylenediaminetetraacetate and sodium gluconate.
[0052] In some embodiments, the alkali of the alkaline etching solution is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and potassium ethoxide.
[0053] In some of the embodiments, the alkaline etching solution further comprises 0.2% to 0.5% of a surfactant by mass percentage.
[0054] In some embodiments, the surfactant of the alkaline etching solution is selected from one or both of isooctyl alcohol polyoxyethylene ether phosphate and fast penetrant T.
[0055] Alternatively, the isooctyl polyoxyethylene ether phosphate component may include one or both of OEP-98 and OEP-70.
[0056] In some of the embodiments, the alkaline etching solution further comprises 1% to 3% of an auxiliary agent by mass percentage.
[0057] In some embodiments, the auxiliary agent of the alkaline etching solution includes one or both of borate compounds and polyol compounds, wherein the polyol compound refers to an alcohol compound containing two or more hydroxyl groups in the molecule.
[0058] In some embodiments, the borate compound is selected from one or a mixture of sodium tetraborate, potassium tetraborate and sodium perborate.
[0059] In some embodiments, the polyol compound is selected from one or more of glycerol, ethylene glycol and diethylene glycol.
[0060] In some embodiments, the alkali treatment step includes: immersing the base glass in an alkaline etching solution.
[0061] In some embodiments, the alkali treatment is carried out at a temperature of 50° C. to 90° C. and for a time of 30 min to 120 min.
[0062] Alkali treatment can effectively reduce the microcracks of base glass, thereby improving the impact resistance of glass. However, alkali treatment has limited effect on the strength of tempered glass. While eliminating microcracks, it will also cause new defects due to erosion. For example, the surface of pre-treated glass after alkali treatment will generate additional silicon-oxygen bonds and silicon hydroxyl groups, resulting in a decrease in product performance. The -SiOH sites on the glass surface are fixed and cannot move, have low reactivity, and the presence of metal oxides on the surface of the base glass further hinders the efficiency of theoretically feasible reactions, resulting in a lack of effective treatment methods for broken silicon-oxygen bonds on the glass surface after alkali treatment.
[0063] In view of the above problems, the glass strengthening method of the present application further comprises the step of acid-treating the pre-treated glass using an organic acid treatment liquid, wherein the organic acid treatment liquid comprises water and an organic acid.
[0064] Further, the mass concentration of fluoride ions in the organic acid treatment solution is less than 0.5%. Optionally, the mass concentration of fluoride ions in the organic acid treatment solution is less than 0.05%.
[0065] Organic acids have the characteristics of small steric hindrance and high reactivity. Using organic acid treatment liquid to treat pretreated glass can reconnect broken silanol bonds (silicon oxygen bond hydrolysis) through dehydration condensation reaction, obtain glass with better microstructure integrity and stronger rigidity, and effectively improve the impact resistance of strengthened glass. In addition, organic acids usually have good complexing ability and are easy to adsorb and combine with metal substances on the surface of glass. They can not only play a role in removing impurities on the surface of glass, but also make organic acids easy to adsorb on the surface of glass, and then react effectively with silanol bonds, effectively improving the integrity of the microstructure of the glass surface.
[0066] In some embodiments, the acid treatment step includes: immersing the base glass in an organic acid treatment solution.
[0067] In some of the embodiments, the organic acid content of the organic acid treatment liquid is 3% to 15% in terms of mass percentage of the organic acid treatment liquid. When the concentration of the organic acid is too low, the efficiency of the acid treatment is low, and as the soaking time increases, the organic acid will gradually oxidize, resulting in a further decrease in efficiency and affecting the treatment effect; and if the organic acid concentration is too high, the organic acid is also more susceptible to oxidation, which may produce side reactions and affect the treatment effect. Optionally, the content of the organic acid can be, but is not limited to, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or other parameters within the range of 3% to 15%.
[0068] In some embodiments, the temperature of the acid treatment is 50°C to 90°C. The temperature of the acid treatment should not be too low, otherwise the polycondensation reaction between the organic acid and the silanol group will be difficult to proceed, and it will be difficult to achieve an effective modification effect; if the temperature is too high, the organic acid will be easily oxidized, which will not only affect the treatment effect, but also reduce the service life of the organic acid treatment solution. Optionally, the temperature of the acid treatment can be but is not limited to 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or other parameters within the range of 50°C to 90°C.
[0069] In some embodiments, the time of acid treatment is 2min~180min. The time of acid treatment is too short to obtain effective strengthening effect. And because the polycondensation reaction of organic acid and silanol is a reversible reaction, after reaching reaction equilibrium, the effect of continuing to extend the reaction time is not obvious. In this application, the time of acid treatment includes but is not limited to 2min, 5min, 8min, 10min, 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 60min, 70min, 80min, 90min, 100min, 120min, 140min, 160min, 180min or other parameters within the range of 2min~180min.
[0070] In some embodiments, the acid treatment time is 2 min to 45 min.
[0071] In some embodiments, the organic acid includes one or more of hydroxyethylidene diphosphonic acid (HEDP), citric acid, itaconic acid, m-phenylenedisulfonic acid, aminotrimethylphosphonic acid, ethylenediaminetetramethylphosphonic acid, phosphonic acid butylamine-1,2,4-tricarboxylic acid, tartaric acid, maleic acid, oxalic acid, malonic acid, 1,4-butanedisulfonic acid and methanedisulfonic acid.
[0072] In some embodiments, the organic acid treatment liquid includes 3% to 15% of hydroxyethylidene diphosphonic acid and 85% to 97% of water, based on the mass percentage of the organic acid treatment liquid. Hydroxyethylidene diphosphonic acid is an organic acid with good water solubility, low steric hindrance and high reactivity. Using hydroxyethylidene diphosphonic acid, the surface treatment of the pre-treated glass can be efficiently completed without adding organic solvents and strong fluorine acids.
[0073] In some embodiments, the organic acid treatment solution further comprises 1% to 30% of an organic solvent in terms of mass percentage of the organic acid treatment solution. The organic cosolvent can increase the solubility of the organic acid in water, thereby improving the reaction efficiency of the acid treatment. Optionally, the mass content of the organic solvent can be, but is not limited to, 1%, 5%, 10%, 15%, 20%, 25%, 30% or other parameters within the range of 1% to 30%.
[0074] In some embodiments, the organic solvent includes one or more of ethylene glycol, glycerol, and polyethylene glycol.
[0075] In some embodiments, the organic acid includes one or more of citric acid, itaconic acid, and isophenyl disulfonic acid. In terms of mass percentage of the organic acid treatment liquid, the organic acid treatment liquid includes 1% to 30% of an organic solvent, 3% to 15% of an organic acid, and 55% to 96% of water.
[0076] In some of the embodiments, the organic acid treatment solution also includes 0.3% to 5% of a fluorine-free inorganic strong acid in terms of mass percentage of the organic acid treatment solution. The introduction of a fluorine-free inorganic strong acid can reduce the pH of the organic acid treatment solution, thereby increasing the reactivity of the organic acid. The amount of fluorine-free inorganic strong acid added should not be too much, and fluoride ions should not be involved to reduce corrosion of the glass. The mass content of the fluorine-free inorganic strong acid can be, but is not limited to, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5% or other parameters within the range of 0.3% to 5%.
[0077] In some embodiments, the fluorine-free inorganic strong acid includes one of sulfuric acid, nitric acid and hydrochloric acid.
[0078] In some embodiments, the organic acid includes one or more of aminotrimethylphosphonic acid, ethylenediaminetetramethylphosphonic acid, phosphonic acid butylamine-1,2,4-tricarboxylic acid, tartaric acid, maleic acid, oxalic acid, malonic acid, 1,4-butanedisulfonic acid and methyl disulfonic acid. In terms of mass percentage of the organic acid treatment liquid, the organic acid treatment liquid includes 0.3% to 5% of a fluorine-free inorganic strong acid, 1% to 30% of an organic solvent, 3% to 15% of an organic acid and 50% to 95% of water.
[0079] The glass strengthening method of the present application causes less damage to the base glass, and thus can be applied to the strengthening treatment of base glasses with different characteristics.
[0080] In some embodiments, the base glass includes base glass processed by one or more of cutting, CNC processing and tempering. Optionally, the base glass includes Corning GG8 tempered glass, Corning GG3 tempered glass and microcrystalline glass.
[0081] The present application does not limit the shape of the basic glass, and the basic glass can be flat glass or curved glass. The curved glass can be single-curved glass, double-curved glass, triple-curved glass, quad-curved glass, special-shaped glass, etc.
[0082] In some other embodiments, the present application also relates to a tempered glass, which is obtained by using the above-mentioned glass tempering method.
[0083] The present application is further described in detail below in conjunction with specific embodiments.
[0084] In the following specific embodiments and comparative examples, the raw materials used, unless otherwise specified, are all commercially available products; the instruments used, unless otherwise specified, are all commercially available products; and the processes used, unless otherwise specified, are all routinely selected by those skilled in the art.
[0085] Example 1
[0086] This embodiment provides a tempered glass, wherein the tempered glass is processed by a glass tempering method to obtain:
[0087] Corning GG8 (161*74mm) was selected as the base glass, and the base glass was treated with an alkaline etching solution. The base glass was immersed in the alkaline etching solution for 45 minutes at a temperature of 80°C to obtain a pretreated glass. The alkaline etching solution consisted of 30wt% NaOH, 5wt% sodium gluconate and 65wt% water in terms of mass percentage.
[0088] The pretreated glass is treated with an organic acid treatment liquid, and the pretreated glass is immersed in the organic acid treatment liquid for 5 minutes at a temperature of 80° C. to obtain a tempered glass. The organic acid treatment liquid is composed of 10% hydroxyethylidene diphosphonic acid and 90% water by mass percentage.
[0089] Example 2
[0090] This embodiment provides a tempered glass.
[0091] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the alkali treatment is 30 minutes.
[0092] Example 3
[0093] This embodiment provides a tempered glass.
[0094] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the alkali treatment is 60 minutes.
[0095] Example 4
[0096] This embodiment provides a tempered glass.
[0097] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the alkali treatment is 80 minutes.
[0098] Example 5
[0099] This embodiment provides a tempered glass.
[0100] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the acid treatment is 2 minutes.
[0101] Example 6
[0102] This embodiment provides a strengthened glass.
[0103] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the acid treatment is 10 minutes.
[0104] Example 7
[0105] This embodiment provides a strengthened glass.
[0106] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the acid treatment is 30 minutes.
[0107] Example 8
[0108] This embodiment provides a strengthened glass.
[0109] The treatment method of the tempered glass in this embodiment is substantially the same as that in Embodiment 1, except that the immersion time for the acid treatment is 120 min and the temperature is 50° C.
[0110] Example 9
[0111] This embodiment provides a strengthened glass.
[0112] The treatment method of the tempered glass in this embodiment is substantially the same as that in the first embodiment, except that the temperature of the acid treatment is 90°C.
[0113] Example 10
[0114] This embodiment provides a strengthened glass.
[0115] The method for treating the tempered glass of this embodiment is substantially the same as that of Embodiment 1, except that, in terms of mass percentage, the organic acid treatment solution is composed of 15% hydroxyethylidene diphosphonic acid and 85% water.
[0116] Embodiment 11
[0117] This embodiment provides a strengthened glass.
[0118] The method for treating the tempered glass of this embodiment is substantially the same as that of Embodiment 1, except that, in terms of mass percentage, the organic acid treatment solution is composed of 10% citric acid and 90% water.
[0119] Example 12
[0120] This embodiment provides a strengthened glass.
[0121] The treatment method of the tempered glass of this embodiment is basically the same as that of Embodiment 1, except that, in terms of mass percentage, the organic acid treatment solution is composed of 10% 1,4-butanedisulfonic acid, 10% ethylene glycol, 1% sulfuric acid and 79% water.
[0122] Comparative Example 1
[0123] This comparative example provides a strengthened glass.
[0124] The treatment method of the tempered glass in this comparative example is different from that in Example 1 in that: after the alkali treatment, no acid treatment is performed.
[0125] Comparative Example 2
[0126] This comparative example provides a strengthened glass.
[0127] The treatment method of ordinary glass in this comparative example is different from that in Example 3 in that: after the alkali treatment, no acid treatment is performed.
[0128] Comparative Example 3
[0129] This comparative example provides a strengthened glass.
[0130] The treatment method of ordinary glass in this comparative example is different from that in Example 4 in that: after the alkali treatment, no acid treatment is performed.
[0131] Comparative Example 4
[0132] This comparative example provides a strengthened glass.
[0133] The treatment method of ordinary glass in this comparative example is different from that in Example 1 in that the alkali treatment time is 120 minutes and no acid treatment is performed after the alkali treatment.
[0134] Comparative Example 5
[0135] This comparative example provides a strengthened glass.
[0136] The treatment method of ordinary glass in this comparative example is different from that in Example 1 in that an inorganic strong acid is used in the acid treatment, and the inorganic strong acid is a 10 wt % sulfuric acid aqueous solution.
[0137] Comparative Example 6
[0138] This comparative example provides a strengthened glass.
[0139] The treatment method of ordinary glass in this comparative example is different from that in Example 1 in that an inorganic strong acid is used in the acid treatment, and the inorganic strong acid is a 10 wt % hydrofluoric acid aqueous solution.
[0140] Comparative Example 7
[0141] This comparative example provides a strengthened glass.
[0142] The treatment method of the ordinary glass in this comparative example is different from that in Example 1 in that: instead of performing alkali treatment, the base glass is directly subjected to acid treatment, and the immersion time for the acid treatment is 30 minutes.
[0143] Comparative Example 8
[0144] The treatment method of the ordinary glass in this comparative example is different from that in Example 1 in that: the base glass is firstly subjected to an acid treatment, and then the acid-treated glass is subjected to an alkali treatment.
[0145] Comparative Example 9
[0146] The treatment method of the ordinary glass in this comparative example is different from that in Example 6 in that: the base glass is firstly subjected to an acid treatment, and then the acid-treated glass is subjected to an alkali treatment.
[0147] Comparative Example 10
[0148] The treatment method of the ordinary glass in this comparative example is different from that in Example 7 in that the base glass is firstly subjected to an acid treatment, and then the acid-treated glass is subjected to an alkali treatment.
[0149] Comparative Example 11
[0150] The treatment method of the ordinary glass in this comparative example is different from that in Example 3 in that: the base glass is firstly subjected to an acid treatment, and then the acid-treated glass is subjected to an alkali treatment.
[0151] Comparative Example 12
[0152] The treatment method of the ordinary glass in this comparative example is different from that in Example 4 in that the base glass is firstly subjected to an acid treatment, and then the acid-treated glass is subjected to an alkali treatment.
[0153] Comparative Example 13
[0154] This comparative example provides a glass substrate, and the glass substrate is Corning GG8 (161*74mm).
[0155] Test Case
[0156] Center drop ball test: Use a cylinder with a metal ball at the end to directly contact the product, and use a 60g weight to hit the cylinder through free fall to achieve the purpose of indirectly hitting the product. The free fall height of the weight ranges from 20cm to 100cm. Start the test from 20cm. If the product does not break after the impact, increase the height by 5cm and hit it again. If the product breaks, record the height value of the unbroken product (for example, if the height is 50cm and the product breaks, the center drop ball records 45cm). The test results of each embodiment and comparative example are shown in Table 1.
[0157] Table 1
[0158]
[0159] From the tests of the above embodiments and comparative examples, it can be seen that the impact resistance of the strengthened glass obtained by the glass strengthening method of the present application, which sequentially performs alkali treatment and acid treatment, has been significantly improved, especially the strengthened glass obtained in Example 4, which has a center drop ball average of more than 100 cm (the upper limit of the center drop ball test is 100 cm, and the actual tolerance is greater than 100 cm). In addition, for organic acids with slightly weak acidity and general water solubility (1,4-butanedisulfonic acid), a good glass strengthening effect can be obtained by adding organic solvents and inorganic strong acids. At the same time, although the method of alkali treatment alone can obtain relatively good impact resistance by extending the treatment time, the improvement of the impact resistance of the glass is limited as the immersion time increases, and after long-term immersion, it may even cause the impact resistance of the glass to decrease. Although there is a certain effect when the base glass is treated with an organic acid alone, the improvement in impact resistance is not obvious. Also, from Comparative Examples 5 and 6, it can be seen that if the organic acid is replaced with a fluorine-free inorganic strong acid such as sulfuric acid, the impact resistance is not significantly improved, while if it is replaced with 10wt% hydrofluoric acid, the impact resistance will decrease. In addition, Comparative Examples 8 to 12 are control groups in which the order of alkali treatment and acid treatment is exchanged. It can be seen that the improvement of the impact resistance of the glass by the method of acid treatment first and then alkali treatment is small, which may be caused by the further reaction of the alkali treatment with the product after the acid treatment.
[0160] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0161] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims, and the description may be used to interpret the content of the claims.
Claims
1. A glass strengthening method, characterized in that: The following steps are involved: Using an alkaline etching solution to perform an alkali treatment on the base glass to obtain a pre-treated glass; Performing acid treatment on the pretreated glass using an organic acid treatment solution; The organic acid treatment solution includes water and an organic acid.
2. The glass strengthening method according to claim 1, characterized in that: The content of the organic acid is 3% to 15% by mass percentage of the organic acid treatment liquid.
3. The glass strengthening method according to claim 1, characterized in that: In terms of mass percentage, the alkaline etching solution comprises the following components: Alkali 5%~50%; Chelating agent 1%~10%; and Water 40%~94%.
4. The glass strengthening method according to claim 3, characterized in that: The base comprises one or more of potassium hydroxide, sodium hydroxide, potassium carbonate and potassium ethoxide; and / or The chelating agent includes one or more of sodium citrate, disodium edetate and sodium gluconate.
5. The glass strengthening method according to claim 1, characterized in that: The acid treatment time is 2 min to 180 min; and / or The temperature of the acid treatment is 50°C to 90°C; and / or The alkali treatment time is 30min to 120min; and / or The temperature of the alkali treatment is 50°C to 90°C.
6. The glass strengthening method according to claim 1, characterized in that: The organic acid includes one or more of hydroxyethylidene diphosphonic acid, citric acid, itaconic acid, m-benzene disulfonic acid, amino trimethylene phosphonic acid, ethylenediamine tetramethylene phosphonic acid, phosphonic acid butylamine-1,2,4 tricarboxylic acid, tartaric acid, maleic acid, oxalic acid, malonic acid, 1,4-butanedisulfonic acid and methyl disulfonic acid.
7. The glass strengthening method according to any one of claims 1 to 6, characterized in that: The organic acid treatment solution further comprises 1% to 30% of an organic solvent in terms of mass percentage of the organic acid treatment solution.
8. The glass strengthening method according to any one of claims 1 to 6, characterized in that: The organic acid treatment solution further comprises 0.3% to 5% of a fluorine-free inorganic strong acid in terms of mass percentage of the organic acid treatment solution.
9. The glass strengthening method according to any one of claims 1 to 6, characterized in that: The organic acid includes one or more of aminotris(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), phosphonic acid butylamine-1,2,4-tricarboxylic acid, tartaric acid, maleic acid, oxalic acid, malonic acid, 1,4-butanedisulfonic acid and methyl disulfonic acid; The organic acid treatment solution further comprises 1% to 30% of an organic solvent and 0.3% to 5% of a fluorine-free inorganic strong acid, in terms of mass percentage of the organic acid treatment solution.
10. A tempered glass, characterized in that: The glass is obtained by the glass strengthening method according to any one of claims 1 to 9.
Citation Information
Cited By
Chemical polishing reagent as well as preparation method and application thereof
CN116375352A
Chemical Polishing Reagent, Its Preparation Method and Application
CN116375352B
Recycling method of CNC (Computer Numerical Control) glass waste residue
CN120325664A